2020
DOI: 10.1136/bmjmilitary-2020-001406
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Stress fractures in military trainees: a large-scale cohort

Abstract: IntroductionThe Israel Defense Forces (IDF) has strict protocols for the diagnosis and treatment of stress fractures wherein diagnosis is clinical with imaging used for persistent symptoms only. The purpose of this study was to examine the incidence of clinical and radiological stress fractures during IDF combat training.MethodsMedical records of all soldiers enlisted to combat training between 2014 and 2017 were scanned for the diagnosis of stress fractures. We examined the imaging tests ordered (plain radiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…Despite the fact that the clinical prevalence of stress fractures decreased after 8 weeks, incident lower limbs stress fractures persisted for over 20 weeks [8]. Actually, the incidence of stress fractures were higher in female soldiers than men [6].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Despite the fact that the clinical prevalence of stress fractures decreased after 8 weeks, incident lower limbs stress fractures persisted for over 20 weeks [8]. Actually, the incidence of stress fractures were higher in female soldiers than men [6].…”
Section: Introductionmentioning
confidence: 95%
“…Then, in 1897 Stechow found an evidence of fractures on imaging, so he called these fractures by "march fractures" [3,5]. The incidence of stress fractures among military recruits has been estimated to be in the range of 1.9%-31% [6]. In other studies, reported in India the incidences were 11.4% and 7.04% in two different military training centers, The occurrence of SFs was higher during their initial training period and reached its peak at 12 weeks of training [7].…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms increase progressively, culminating in failure of loading or the need to stop the physical activity. SFs should be differentiated from insufficiency fractures that result from normal load on a pathological bone ( 1 , 2 ). This narrative review will explore the main aspects of SFs, including risk factors, pathophysiology, evaluation, and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Stress fractures, either partial or complete, are common overuse injuries caused by a repetitive submaximal bone loading [ 1 ]. The location of the stress fracture varies from sport to sport, but is most commonly observed in the lower extremities [ 2 , 3 ]. They are particularly common in the physically active individuals including but not limited to track and field athletes, long distance runners, dancers, and military recruits [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The location of the stress fracture varies from sport to sport, but is most commonly observed in the lower extremities [ 2 , 3 ]. They are particularly common in the physically active individuals including but not limited to track and field athletes, long distance runners, dancers, and military recruits [ 2 , 3 ]. The prevalence of stress fractures is estimated to be between 6.5–9.7% among athletes of different sport disciplines [ 4 ].…”
Section: Introductionmentioning
confidence: 99%